ANALISIS PENGARUH KREATIVITAS DALAM PERIKLANAN, KEMUDAHAN IKLAN DIINGAT, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi pada Iklan Susu Bear Brand Edisi Kemurnian #YangDipercaya) - Ikhlas, Disa Insanul; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2023)
ABSTRACT This research is motivated by the emergence of various dairy products that are developing in Indonesia, leading each company to compete to maintain their existence in the market, one of which is through advertising. Nestle is one of the companies that actively advertises its products with creative advertisements. However, over the past 3 years, one of Nestle's products, Bear Brand, has not yet reached the top position in consumer preference. This study examines the efforts made by Bear Brand to enhance its presence in the market by improving the perception of value and advertising awareness as effectively as possible. The research was conducted using a questionnaire method, applying purposive sampling techniques to 100 respondents who had previously made purchasing decisions on Bear Brand dairy products. The regression equation yields the following results : Y = 0,064X1 + 0,155X2 + 0,649X3 Where the variables of ad recall (X2) and perceived value (X3) have a positive and significant influence on purchase decisions (Y), while the variable of creativity in advertising (X1) has a positive but not significant influence on purchase decisions. The adjusted R Square value of 0.577 indicates that 57.7% of the purchase decision variables can be explained by the three independent variables in the regression equation. The remaining 42.3% is explained by other variables outside the three variables used in this study